Complementary and alternative medicine use in infertility: A review of infertile women's needs - Farangis Sharifi; Robab Latifnejad Roudsari (Wolters Kluwer Medknow Publications, 2022)
The use of complementary and alternative medicine (CAM) is common in infertile women in different countries. The purpose of the current study was to review the infertile women's needs in relation to CAM use. This narrative review was conducted through searching English databases including Scopus, PubMed, Embase, Web of Science, Cochrane library as well as Persian databases consisted of SID, and Magiran. The used keywords included "CAM/therapy, needs, and Infertility." All studies published in English peer-reviewed journals from conception to October 2020, which examined the infertile women's needs in the field of CAM use were included in the review. In the process of data extraction, two researchers screened the title, abstract, and full text of the articles. Out of the 2166 articles reviewed, 29 articles including six qualitative and mixed methods studies, four review, and 19 quantitative studies met the inclusion criteria. The results showed that infertile women have different needs in six domains consisted of educational and informational needs, the need for psychological counseling, supportive needs, the need for CAM use counseling, the need to treatment consistent with women's culture and demands, and the need to the integration of CAM with conventional medicine. Awareness of infertile women's needs toward CAM use can help health policymakers and planners in designing and implementing counseling services in accordance with the demands and culture of infertile couples. It also helps to develop a coherent program to integrate the use of CAM in the classical infertility treatment.